Seasonal changes in social behavior and movements of bat-eared foxes in South Africa: Disease implications - Kamler, J; Garcia, SA; Macdonald, DW (Oxford University Press, 2017)
Bat-eared foxes (Otocyon megalotis) are the primary vector and maintenance host species for rabies in the western half of South Africa. Reported cases of rabies in this species peak during the dry season, although reasons for this annual peak are unknown. Rabies transmission is dependent on contact rates, thus seasonal differences in social behavior or movements may facilitate increased contact rates in the dry season. During an ecological study of bat-eared foxes in South Africa from 2005-2008, we compared between the wet and dry seasons several aspects of the ecology of bat-eared foxes that presumably would influence contact rates. Bat-eared foxes had significantly larger group sizes in the dry season, which would presumably increase intragroup contact rates, and significantly greater home range sizes, greater home range overlap, and higher rates of excursions (i.e., short-term forays from their home range), which would presumably increase inter-group contact rates. Seasonal differences in behavior and movements of bat-eared foxes likely were related to their reproductive cycle and seasonal availability of food resources. In contrast to previous reports, we documented relatively high rates of physical contact between bat-eared foxes and dogs (Canis familiaris) and black-backed jackals (Canis mesomelas), suggesting there is potential for bat-eared foxes to transmit the rabies virus to larger canids in the region. We provide recommendations for control of rabies outbreaks in bat-eared foxes if it becomes a health or management concern.